Creating joint experiences - Families engaging with a heritage site. (June 2020) - Melvin, John; Winklhofer, Heidi; McCabe, Scott
Abstract: Interactions between family members constitutes an important element of engagement with tourism sites, leading to enhanced value creation. Yet we know little about how these engagement practices lead to experience outcomes. Studies of visitor engagement have explored C2C value co-creation contexts, adding to our understanding of social practices as a source of value outcomes. This study adds to this literature through a focus on the intimate social context of families' collective engagement practices, viewing the family unit as constituting a complex amalgam of individual, relational and collective resources (Epp & Price, 2008). Adopting a multi-stage and multi-method qualitative research design, we identify seven practices through which families engage with attractions, including: absorbing, interacting, information sharing, explaining, constructing meaning, competing and deviating. Families associate these practices with experience outcomes: bonding, creating memories, entertainment, and learning. The findings inform the design of effective engagement platforms and resource deployment to facilitate group experiences. Highlights: Identifies family engagement practices with tourist attractions and, how their engagement contributes to their individual and collective experience. Highlights the resources and relational structures that shape engagement practices, and experience outcomes. Offers insights into the importance of children's contributions to families' shared service experiences. Findings inform the design of effective engagement platforms to facilitate group experiences.